Observation of the swallowing process by application of videofluoroscopy and real-time magnetic resonance imaging – consequences for retronasal aroma stimulation. - Büttner, Andrea; Beer, Ambros; Hannig, Christian; et al. (Chemical Senses, 2001)
The process of eating and drinking was observed in vivo by application of videofluoroscopy, a dynamic X-ray technique, as well as real-time magnetic resonance imaging. The study was aimed at elucidating the timing and performance of the physiological organs involved in mastication and swallowing, mainly the tongue, the pharynx and the soft palate (velum palatinum). It was shown for the first time that effective physiological barriers do exist during food consumption that are capable of retaining volatiles such as helium within the oral cavity. These barriers allow the access of odorants to the nasal cavity only at certain times during the eating process. Their effectiveness is related to the texture of the food as well as the amount of food material present in the oral cavity and, thereby, directly influences retronasal aroma perception.<br